2020
DOI: 10.1186/s11658-020-00235-8
|View full text |Cite
|
Sign up to set email alerts
|

Knockdown of LINC00665 inhibits proliferation and invasion of breast cancer via competitive binding of miR-3619-5p and inhibition of catenin beta 1

Abstract: Background Long intergenic non-protein coding RNA00665 (LINC00665) plays a crucial tumorigenic role in many cancers, such as gastric cancer and lung adenocarcinoma. However, its role and mechanism of action in the progression of breast cancer (BC) are unknown. Methods LINC00665 expression levels were determined using quantitative polymerase chain reaction analysis with BC tissues and cell lines. BC cell proliferation was tested by performing 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide assays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(24 citation statements)
references
References 20 publications
0
24
0
Order By: Relevance
“…One of the mechanisms by which lncRNAs are implicated in tumorigenesis is acting as competing endogenous RNAs (ceRNA) of microRNA (miRNA) and thereby facilitating the transcription of target mRNAs [ 12 , 13 ]. Up to now, long intergenic non-protein-coding RNA 665 (LINC00665) has been found to show a higher expression pattern in cancers and to be closely implicated in carcinogenesis, including breast cancer [ 14 ], prostate cancer [ 15 ], gastric cancer [ 16 ], colorectal cancer [ 17 ], and ovarian cancer [ 18 ]. Shan et al [ 19 ] found that LINC00665 level was increased in HCC tissues and cells and associated with shorter overall survival, and depletion of LINC00665 repressed cell viability and promoted cell apoptosis and autophagy in HCC via the miR-186-5p/MAP4K3 axis.…”
Section: Introductionmentioning
confidence: 99%
“…One of the mechanisms by which lncRNAs are implicated in tumorigenesis is acting as competing endogenous RNAs (ceRNA) of microRNA (miRNA) and thereby facilitating the transcription of target mRNAs [ 12 , 13 ]. Up to now, long intergenic non-protein-coding RNA 665 (LINC00665) has been found to show a higher expression pattern in cancers and to be closely implicated in carcinogenesis, including breast cancer [ 14 ], prostate cancer [ 15 ], gastric cancer [ 16 ], colorectal cancer [ 17 ], and ovarian cancer [ 18 ]. Shan et al [ 19 ] found that LINC00665 level was increased in HCC tissues and cells and associated with shorter overall survival, and depletion of LINC00665 repressed cell viability and promoted cell apoptosis and autophagy in HCC via the miR-186-5p/MAP4K3 axis.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that overexpression of Linc00665 can enhance the invasion and metastasis of various tumors, which supports our speculation. Yu et al reported that Linc00665 deletion can inhibit the migration and invasion of triple negative breast cancer cell lines MDA-MB-231 and BT549 ( 12 , 31 ). Gao et al elucidated that Linc00665 knockdown can inhibit the migration and invasion of gastric cancer cell lines AGS and BGC‐823 ( 9 ).…”
Section: Discussionmentioning
confidence: 99%
“…Lu et al analyzed the expression level of LINC00665 in breast cancer tissues and matched normal tissues in the database ( Lv et al, 2020 ). They found that the expression of the LINC00665 was significantly upregulated in breast cancer tissues ( Lv et al, 2020 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%
“…Lu et al analyzed the expression level of LINC00665 in breast cancer tissues and matched normal tissues in the database ( Lv et al, 2020 ). They found that the expression of the LINC00665 was significantly upregulated in breast cancer tissues ( Lv et al, 2020 ). Subsequently, they used qRT-PCR to identify LINC00665 expression in 106 pairs of breast cancer tissues and adjacent normal tissues and also proved that LINC00665 was highly expressed in breast cancer tissues ( Lv et al, 2020 ).…”
Section: Function Of Linc00665 In Cancers and Underlying Molecular Me...mentioning
confidence: 99%